How lighting intensity influence diners' communication performance in restaurant : a comparative study between Jibril, SS15 Subang Jaya and Ink Library, Eco Grandeur / Batrisyia Nazri and Farid Al Hakeem Yuserrie - Nazri, Batrisyia; Yuserrie, Farid Al Hakeem (2019)
This study identifies the lighting intensity used in restaurant, the communication performance of the diners, and study how the lighting intensity influence diners' communication performance in restaurant. Two restaurants with different lighting intensity was chosen for the study by distributing the same questionnaire to 25 people in each restaurant while observing the communication performance of diners. Data were analysed and compared where it is found that most diners in restaurant with low lighting intensity were aware that the lighting is insufficient and should be brighter while those in higher intensity lighting felt the lighting is sufficient and should not be brighter. The comfort levels of diners communicating in lower intensity were rather dispersed while those in higher intensity lighting all felt comfortable communicating. From the observations, it is found that diners in lower intensity light communicates in a shorter span with longer intervals while those in higher intensity lighting communicates in longer span with minimal to none intervals. It is identified that the intensity of lighting affects the communication performance of diners, though their comfort in communicating with lower intensity lighting depends on the individual. Restaurant owners should take lighting into consideration as it influences diners comfort and communication performance.